2016
DOI: 10.7812/tpp/15-220
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Value of High-Quality Care for Work-Associated Carpal Tunnel Syndrome in a Large Integrated Health Care System: Study Design

Abstract: The timing of diagnosis varied, but time off work was generally short and related to surgery. If associations of quality of care with key medical, economic, and quality-of-life outcomes are identified for work-associated CTS, systematic efforts to evaluate and improve quality of medical care for this condition are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…This comparison may be helpful clinically in identifying a subgroup of patients with significant motor weakness, as well as quantifying the amount of motor loss. 26 The main limitations of this study stem from its retrospective nature. We had 36% males since the study was performed in a "blue collar" area with a relatively high percentage of laborers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This comparison may be helpful clinically in identifying a subgroup of patients with significant motor weakness, as well as quantifying the amount of motor loss. 26 The main limitations of this study stem from its retrospective nature. We had 36% males since the study was performed in a "blue collar" area with a relatively high percentage of laborers.…”
Section: Discussionmentioning
confidence: 96%
“…[23][24][25] Other studies have evaluated the effect of accurate diagnosis. 26 The best method to diagnose CTS has long been debated in the literature. 27,28 Sometimes considered an occupational condition, the need for a standardized, objective, and reliable diagnostic tool has not consistently been met.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate quality of care, we reviewed electronic medical records. To assess outcomes, survey researchers interviewed subjects by telephone at baseline (August 2011–March 2013) and at follow‐up (May 2013–October 2014) …”
Section: Methodsmentioning
confidence: 99%
“…10 (August 2011-March 2013) and at follow-up (May 2013-October 2014). 11,12 Participants. Specialists in 30 KPNC Occupational Health Centers treat 45,000 individuals with workers' compensation claims annually.…”
Section: Methodsmentioning
confidence: 99%
“…We found that, during the first year of treatment, 80% of care for CTS adhered to the quality measures' basic standards. Notably, receiving better care was associated with larger improvements in patient‐reported symptoms of CTS, CTS‐related functional status, and overall health‐related quality of life over an 18‐month follow‐up period …”
Section: Introductionmentioning
confidence: 98%